Asociación entre la enfermedad inflamatoria pélvica y la infertilidad femenina - Carrion Gallardo, Maria Jose (Machala : Universidad Técnica de Machala, 2023)
Background - Pelvic inflammatory disease (PID) is an inflammatory pathology that can be caused by a variety of microbiological agents and affects the upper portion of the female reproductive tract, including the uterus (endometritis), fallopian tubes (salpingitis), tubal abscess- ovarian disease and pelviperitonitis, which in turn can trigger serious changes in female fertility. Aim- To determine the association between the appearance of pelvic inflammatory disease and the development of female infertility. Conclusions - The diagnosis of pelvic inflammatory disease can be expected as a risk factor for the development of female infertility. The exact mechanism of its pathogenesis is not known, but among the most accepted theories, it has been concluded that infectious processes at the level of the upper female reproductive tract cause tissue damage from the first episode, subsequently hindering the consolidation of the fertilized ovum. Long-term follow-up is necessary to assess the association between the pathogens, their affectation in the upper tract, and the risk of generating sequelae in reproductive health. Understanding all of these factors will help guide efforts to prevent the development of female fertility problems in the near future.
Antecedentes - La enfermedad inflamatoria pélvica (EPI) es una patología inflamatoria que puede ser causada por una variedad de agentes microbiológicos y afecta la porción superior del tracto reproductivo femenino, incluyendo el útero (endometritis), las trompas de Falopio (salpingitis), el absceso tubo-ovárico y pelviperitonitis, pudiendo desencadenar a su vez alteraciones en la fertilidad femenina graves. Objetivo - Determinar la asociación entre la aparición de enfermedad inflamatoria pélvica y el desarrollo de infertilidad femenina. Conclusiones - El diagnóstico de enfermedad inflamatoria pélvica puede considerarse como un factor de riesgo para el desarrollo de infertilidad femenina. No se conoce el mecanismo exacto de su patogenia, pero entre las teorías más aceptadas, se ha concluido que el los procesos infecciosos a nivel del tracto reproductivo femenino superior causan daño en los tejidos desde un primer episodio, dificultando posteriormente la implantación del óvulo fecundado. Es necesario un seguimiento a largo plazo para evaluar la asociación entre los patógenos, su afectación al tracto superior y el riesgo de generar secuelas en la salud reproductiva. Comprender todos estos factores, ayudará a guiar los esfuerzos para prevenir el desarrollo de problemas en la fertilidad femenina en un futuro próximo.
Keywords: ENFERMEDAD INFLAMATORIA PELVICA; INFERTILIDAD; VAGINOSIS BACTERIANA; TRICOMONIASIS VAGINAL